Factors Associated With Increased Risk of Pediatric Orbital Cellulitis—Who Should Be Scanned?. Issue 12 (20th December 2021) - Ohana-Sarna-Cahan, Lea; Hurvitz, Noa; Gross, Itai; Cohen, Adi; Hashavya, Saar
Abstract : Background: Evaluation of a child with POC/OC is complicated due difficulties in physical examination and risks of imaging by computed tomography. Method: Retrospective review of children 0–16 years admitted to the pediatric emergency department for POC/OC from 2009 to 2019. Results: Ten years study period, 243 children younger than 16 years presented to the pediatric emergency department with a diagnosis of POC/OC. OC was documented in 51 (20.6%) patients. The mean age was 7.8 years (±4.3 years). Fever (80.4%), upper respiratory tract infection (43%), swelling of both eyelids (96%), proptosis (33.3%), and tenderness on percussion (24.5%) were more common in comparison to POC ( P = 0.0001, 0.03, 0.0001, 0.0001, 0.0001 respectively). All children with suspected diagnosis of OC underwent computed tomography scan. POC accounted for 196 patients. Mean age was 4.6 (±4.3) years. Twenty percent of the cases were recorded as local trauma or insect bite in the infected eye. Mean leukocyte count in the OC group had higher mean of 15.2 (10 9 /L) versus 13.4(10 9 /L) ( P = 0.05), absolute neutrophil count was significantly higher in the OC 11.3(10 9 /L) versus 7.2(10 9 /L) ( P = 0.0001) whereas the lymphocyte count was higher in the POC 4.5(10 9 /L) versus 2.4(10 9 /L) ( P = 0.0001), NLR of 0.318 correlates with orbital cellulitis with sensitivity of 75.5% and specificity of 77.4%. Patients with OC had mean C-reactive protein levels of 11.7 (mg/dL) versus 4.9(mg/dL) ( P = 0.0001), erythrocyte sedimentation rate was elevated in the OC 53.6 (cm/h) versus 36.4 (cm/h) ( P = 0.02). Based on the aforementioned study a risk calculator for OC was formulated with 6 major variables. Conclusions: Differentiation between POC/OC is cardinal. This study highlights the importance of ancillary laboratory tests especially C-reactive protein in the assessment of infections of the eye.